A new high-pressure polymeric nitrogen phase in potassium azide. Issue 16 (21st January 2015) - Zhang, Meiguang; Yan, Haiyan; Wei, Qun; Liu, Hanyu
Abstract : The ELF distributions of 2D "N6 " rings along the c -axis in P 6/ mmm -KN3 (left) and 3D "N6 " rings along the b -axis in C 2/ m -N-KN3 (right). Abstract : To explore new stable polymeric nitrogen phases in alkali metal azides, the crystalline structures of potassium azide KN3, are systematically investigated up to 400 GPa by using unbiased structure searching methods combined with first principles density functional calculations. Two high-pressure phases of KN3, insulator C 2/ m phase with N 3− anions and metallic P 6/ mmm phase with "N6 " rings were uncovered above 20 GPa and 41 GPa, respectively, which are consistent with recent theoretical works. Above 274 GPa, a stable C 2/ m -N phase featuring polymerized N is identified for the first time and it is energetically much superior to the previously proposed C 2/ m -II structure. This C 2/ m -N structure consists of zig-zag N polymer nets which can be naturally viewed as the polymerization of "N6 " molecules rings in the low-pressure P 6/ mmm phase under increasing pressure. Furthermore, the structure evolutions and accompanied chemical bonding behavior of KN3 under pressure are also discussed.